PBMCs gene expression predicts liver fibrosis regression after successful HCV therapy in HIV/HCV-coinfected patients - Virseda-Berdices, Ana; Brochado-Kith, Óscar; Berenguer, Juan; González-García, Juan; Pérez-Latorre, Leire; Busca, Carmen; Díez, Cristina; Micán, Rafael; Fernández-Rodríguez, Amanda; Jiménez-Sousa, María Ángeles; Resino, Salvador (Frontiers in Pharmacology, 2025)
BackgroundHCV eradication with antiviral treatment reduces hepatic disease, but some patients remain at risk of progression to cirrhosis despite HCV clearance. We aimed to examine the association between peripheral blood mononuclear cells (PBMCs) gene expression before HCV therapy and a pronounced decrease in the liver stiffness measurement (LSM) value in HIV/HCV-coinfected patients after HCV treatment and achievement of sustained virological response (SVR).MethodsWe performed a retrospective study in 48 HIV/HCV-coinfected patients who started anti-HCV treatment with at least advanced fibrosis (LSM ≥9.5). Total RNA was extracted from PBMCs at baseline, and poly(A) RNA sequencing was performed. The outcome was an LSM reduction greater than 50% (LSMred>50%) about 48 weeks after HCV treatment.ResultsSeven patients (14.5%) reduced LSM by over 50%. We found 47 significant differentially expressed (SDE) genes associated with reaching an LSMred>50% after achieving HCV eradication, 42 upregulated and 5 downregulated in the LSMred>50% group. Ten and five of these upregulated genes were classified into two significantly enriched KEGG pathways: cell cycle and progesterone-mediated oocyte maturation (q-value <0.05), respectively. Two SDE genes achieved excellent discrimination ability: NCAPG had an AUROC of 0.908, NHLRC1 of 0.879, and a logistic regression model with these two genes of 0.955.ConclusionA pre-treatment gene expression signature in PBMCs was associated with liver fibrosis regression (LSMred>50%) after achieving HCV clearing with HCV therapy in HIV/HCV-coinfected patients, where two SDE genes (NCAPG and NHLRC1) showed the greatest predictive capacity, which could be used as a noninvasive marker of liver fibrosis regression.